2020
DOI: 10.36660/ijcs.20200130
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Pediatric Cardiac Intensive Care Unit

Abstract: Congenital heart defect commonly requires care in pediatric intensive care unit (PICU). They are a heterogeneous group of disorders with an annual incidence of 25,757 new cases in Brazil, 12 cases per 1,000 inhabitants 1. In this paper, Guimarães et al., 2 published a cross-sectional study to describe the epidemiology of patients admitted to PICU from a tertiary hospital in Brazil. In this editorial, we review recent progress in understanding the risk factors for mortality in PICU. The editorial was produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Thrombocytopenia may occur because of the inflammatory response to CPB, the activation of inflammatory cytokines, and autoimmune reactions (9). A higher RACHS-1 level is also directly related to increased postoperative complications (10). In our study, the RACHS-1 score was not significantly related to mortality.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Thrombocytopenia may occur because of the inflammatory response to CPB, the activation of inflammatory cytokines, and autoimmune reactions (9). A higher RACHS-1 level is also directly related to increased postoperative complications (10). In our study, the RACHS-1 score was not significantly related to mortality.…”
Section: Discussioncontrasting
confidence: 45%
“…It was concluded that age, weight, RACHS-1 score, and need for CPB had no significant relationship with the mortality rates (11). Some studies have mentioned that CPB can initiate the inflammatory response (9) and linked a longer CPB time and more complicated surgery (higher RACHS-1) with more postoperative complications (10). The different activities of the surgical centers can justify the contrasting results of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation